2022
DOI: 10.1136/bmjopen-2021-060390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on healthcare service use for non-COVID-19 patients in Japan: retrospective cohort study

Abstract: ObjectivesWe aimed to investigate the impact of the first and second waves of the COVID-19 pandemic on healthcare service use by non-COVID-19 patients.DesignRetrospective cohort study.SettingHospital-based claims database from anonymised hospitals in Japan.ParticipantsPatients (n=785 495) who visited and/or were hospitalised in 26 anonymised hospitals in Japan between January 2017 and November 2020.Outcome measuresWe compared changes in the monthly number of hospitalisations (overall or by diagnosis), outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
3
26
0
1
Order By: Relevance
“…Reasons to justify the low patient patronage was negative image of public hospitals in local media 40 . Consistent with reports across the World, a study conducted in Japan demonstrated a decrease in outpatient clinic prescriptions, with drugs for respiratory diseases most affected and antineoplastic least affected 41 , it correlates with other studies carried out in Japan that revealed a temporary decline in physician visit by patients with chronic conditions 42 . A study carried out in Korea reported a decline in outpatient visits for all cause and chronic diseases than was expected in 2020 43 , in this study there were discrepancies in clinic attendance amongst patients with different chronic diseases, the decline in outpatient visits were more pronounced in these with respiratory, neurological and liver diseases (11.5%,7.1% and 6.2%) respectively, it was less with diabetes, malignant neoplasm , heart disease, thyroid conditions and mental and behavioral disorders 43 .…”
Section: Impact On Health Care Settingssupporting
confidence: 89%
See 1 more Smart Citation
“…Reasons to justify the low patient patronage was negative image of public hospitals in local media 40 . Consistent with reports across the World, a study conducted in Japan demonstrated a decrease in outpatient clinic prescriptions, with drugs for respiratory diseases most affected and antineoplastic least affected 41 , it correlates with other studies carried out in Japan that revealed a temporary decline in physician visit by patients with chronic conditions 42 . A study carried out in Korea reported a decline in outpatient visits for all cause and chronic diseases than was expected in 2020 43 , in this study there were discrepancies in clinic attendance amongst patients with different chronic diseases, the decline in outpatient visits were more pronounced in these with respiratory, neurological and liver diseases (11.5%,7.1% and 6.2%) respectively, it was less with diabetes, malignant neoplasm , heart disease, thyroid conditions and mental and behavioral disorders 43 .…”
Section: Impact On Health Care Settingssupporting
confidence: 89%
“…The first wave signaled the most significant decrease in hospitalization in Japan, particularly in May,2020. This decrease was particularly striking in pediatric care as it persisted through till November,2020, this was mainly due to a reduction in respiratory diseases 41 , even though admissions were low, there was no observed increase in mortality in the ensuing months 41 . In Croatia a survey carried out showed that general admissions fell by 21% over the study period 85 , the greatest dip in admission was witnessed in April 2020, after WHO declared COVID-19 a pandemic 85 .…”
Section: Impact On Health Care Settingsmentioning
confidence: 98%
“…Numbers do not always add up due to missing values. Total (n = 59,707) Primary (n = 2004) Secondary (n = 41,420) Tertiary (n = 16,283) p-value Vital signs Temperature (°C) 37 [36.6, 37.8] 37 [36.6, 37.7] 37 [36.6, 37.7] 37.1 [36.6, 37.8] <0.001 Heart rate (beats/minute) 86 [76, 98] 87 [76, 98] 86 [75, 98] 87 [76, 99] <0.001 Respiratory rate (breaths/minute) 18 [ 16 , 21 ] 18 [ 16 , 20 ] 18 [ 16 , 21 ] 19 [ 16 , 23 ] <0.001 Systolic blood pressure (mmHg) 127 [114, 142] 125 [113, 138] 127 [114, 142] 127 [114, 142] <0.001 Diastolic blood pressure (mmHg) 79 [70, 88] 80 [70, 88] 79 [70, 88] 78 [69, 88] <0.001 Severity of COVID-19 Severe 19975 (33.5) 525 (26.2) 12142 (29.3) 7308 (44.9) <0.001 Non-severe 39732 (66.5) 1479 (73.8) 29278 (70.7) 8975 (55.1) Oxygen support Yes 10401 (17.4) 209 (10.4) 5541 (13.4) 4651 (28.6) <0.001 Route of oxygen support Nasal cannula 6265 (60.2) 159 (76.1) 3953 (71.3) 2153 (46.3) Face mask 1885 (18.1) …”
Section: Resultsmentioning
confidence: 99%
“…no caregiver at home) rather than medical indications. The COVID-19 pandemic has had a significant negative impact on the management of other diseases [ 21 , 22 ]. It is crucial to develop a healthcare resource allocation strategy that takes a view of the entire picture as opposed to focusing on COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…MHLW recommended to avoid Three Cs (Closed spaces, Crowded places, and Close-contact settings) to prevent COVID-19 transmission 8 and behaviour of the general population drastically changed. The number of healthcare facility visits and the consumption of antimicrobials decreased substantially after the emergence of COVID-19 in Japan 9,10 . In short, the COVID-19 pandemic changed the Japanese way of life substantially.…”
Section: Introductionmentioning
confidence: 99%